Method for preparing building daylighting panel by using waste polycarbonate plastic

The method addresses the limitations of recycling waste polycarbonate plastics by enhancing optical and mechanical properties through chemical modification and extrusion molding, achieving high-quality, cost-effective, and environmentally friendly building skylights.

CN119192814APending Publication Date: 2024-12-27HUNAN ZHONGKE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720913.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing methods for recycling waste polycarbonate plastics into building skylights face challenges in achieving optimal optical and mechanical properties, processing complexity, and high production costs, leading to reduced durability and increased environmental pollution.

Method used

A method involving the collection, pretreatment, synthesis of a modified organic compound, and melt blending of waste polycarbonate plastics with 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone to enhance material properties, followed by extrusion molding to form building skylight panels.

Benefits of technology

The method significantly improves optical performance, mechanical strength, and processing efficiency while reducing environmental impact, resulting in high-quality, cost-effective skylight panels with enhanced durability and energy efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly materials, and particularly relates to a method for preparing a building daylighting panel from waste polycarbonate plastics, and the daylighting panel prepared by the method not only has excellent daylighting performance, but also has excellent fireproof performance, uvioresistant performance and thermal insulation performance. Through interaction of the modified compound and the polycarbonate plastic and special treatment in the processing process, the fireproof grade of the daylighting panel reaches B1 or above, and fire spreading can be effectively prevented; in addition, the special formula and structural design of the material also endow the material with a certain heat preservation and insulation effect, so that the energy consumption of buildings is reduced, and the energy utilization efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of environmentally friendly material preparation, and in particular to a method for preparing a building lighting panel by utilizing waste polycarbonate plastic. Background Art

[0002] With the booming development of the construction industry today, building skylights, as an important building material, are widely used in many fields such as industrial plants, commercial buildings, and agricultural greenhouses. Traditionally manufactured building skylights mostly use new polycarbonate plastics, which consumes a huge amount of raw material resources. At the same time, the extensive use of plastic products has led to the accumulation of waste polycarbonate plastics, which has become a serious environmental problem. At present, there are limited ways to recycle and reuse waste polycarbonate plastics. The common treatment method is to simply process them into low-value-added products, which is difficult to convert them into materials that can meet the performance requirements of building skylights. On the one hand, the existing recycling technology fails to fully improve the material properties of waste polycarbonate plastics when processing waste polycarbonate plastics. For example, in terms of optical properties, the transmittance and haze of the prepared skylights are not ideal, which affects the lighting effect and indoor visual comfort; in terms of mechanical properties, the skylights made of recycled materials are insufficient in strength and toughness, and are difficult to withstand external impacts and loads such as wind pressure and snow pressure in the natural environment, which reduces the service life and safety of the skylights. On the other hand, during the processing process, waste polycarbonate plastics have problems such as difficulty in processing and poor molding effect due to their characteristics, resulting in low product qualification rate and increased production costs. For example, the patent number is CN 221837849 U. Although the flexible sunshade cloth is arranged in the main body of the lighting board to adjust the amount of daylighting, the cost of installing an additional sunshade device by the user is reduced to a certain extent. However, in actual use, the durability of the flexible sunshade cloth of the lighting board is problematic. After long-term pulling and the influence of light and temperature changes, it is easy to wear, age or even damage, affecting the long-term stability of its sunshade and lighting adjustment functions. Moreover, in the production process of the lighting board of this structure, since it is necessary to set a cavity, a slide groove and install related pushing components inside, the production process is relatively complicated, which increases the production cost and production cycle, and is not conducive to large-scale industrial production. CN 221957083 U effectively solves the problems of waterproofing and glass plate stability by setting structures such as a reinforcement frame, an upper waterproof board, and a lower waterproof board, but the structural design of the lighting board is relatively complex, resulting in its overall weight being heavy. During the installation process, more manpower and material resources are required for handling and installation, which increases the difficulty and cost of construction. CN 222004430 U The device can effectively treat the dust on the surface of the skylight board and improve the surface quality of the skylight board, but it only focuses on the coating process in the production process of the skylight board, and does not involve the material performance and structural improvement of the skylight board itself. Moreover, when treating dust, the device mainly relies on high-pressure nozzles and scrapers, and has limited cleaning effect on some stubborn stains or sticky dust, which may lead to incomplete cleaning of the skylight board surface, affecting the quality of subsequent coating and the light transmission performance of the skylight board.

[0003] To sum up, the existing patent technologies related to skylight panels have certain defects in different aspects, such as the stability of material properties, the complexity of structure, the limitations of production processes and the adaptability of equipment. These defects limit the further promotion and application of skylight panels in the field of construction. Therefore, it is necessary to develop a new method for preparing building skylight panels using waste polycarbonate plastics to overcome the shortcomings of the existing technology and improve the comprehensive performance and economic benefits of skylight panels. Summary of the invention

[0004] The present invention provides a method for preparing a building lighting panel by using waste polycarbonate plastic, comprising the following steps: (1) Collection of waste polycarbonate plastics: Collect waste polycarbonate plastic materials from electronic and electrical waste dismantling plants, construction waste recycling stations, plastic product recycling points and other sources; (2) Pretreatment: Cleaning: Use professional detergent and clean water to clean the collected waste polycarbonate plastics multiple times to remove dirt, oil and other impurities on the surface; Drying: Put the cleaned waste polycarbonate plastic into a drying oven and dry it at 60-80℃ for 4-6 hours to control the water content of the plastic below 0.3%; Crushing: The dried waste polycarbonate plastic is crushed into small particles by a crusher, and the particle size is controlled between 1-3 mm; (3) Synthesis of modified compounds: 4,4'-dihydroxydiphenyl sulfone and 3-chloro-1-propanol are used as raw materials and reacted under alkaline conditions with sodium hydroxide as a catalyst to synthesize a modified organic compound named 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone. The reaction equation is: .

[0005] The synthesis comprises the following specific steps: adding 400 g of 4,4'-dihydroxydiphenyl sulfone and 300 g of 3-chloro-1-propanol into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and then slowly adding 200 g of sodium hydroxide as a catalyst, placing the reaction system in an oil bath, controlling the reaction temperature at 80-100°C, setting the stirring speed at 400-600 rpm, and reacting for about 5-7 hours. After the reaction is completed, neutralizing and washing with a dilute hydrochloric acid solution to remove excess alkali, and then drying with anhydrous sodium sulfate, and finally obtaining the pure modified organic compound by recrystallization and the like, with a yield of about 500-600 g. (4) Mixing modification: The pretreated waste polycarbonate plastic particles are mixed with the synthesized modified organic compound at a mass ratio of 1:6 to 1:3, and the modified organic compound is ensured to be evenly distributed in the waste polycarbonate plastic particles by setting the stirring speed to 900-1200 rpm and the stirring time to 25-35 minutes; (5) Melt blending: Place the mixed materials into a twin-screw extruder for melt blending, set the temperature to 220°C to 250°C, the screw speed to 300-400 rpm, and the blending time to 15-25 minutes; (6) Molding: Extrusion molding: The melt-blended composite material is extruded through an extruder into the plate shape required for the building skylight board. By adjusting the parameters such as the die size and extrusion speed of the extruder, the extrusion thickness can be adjusted between 2-10 mm according to the design requirements of the specific building skylight board; Cooling and shaping: The skylight board prototype after extrusion molding is cooled and shaped in a cooling device. The cooling time is set to 15-30 minutes, and the water temperature is controlled at 20-30°C. The skylight board is slowly cooled and shaped to obtain the final building skylight board product.

[0006] Furthermore, by setting the stirring speed to 900-1200 rpm and the stirring time to 25-35 minutes, it is ensured that the modified organic compound is evenly distributed in the waste polycarbonate plastic particles.

[0007] Furthermore, in the cleaning step of the pretreatment, cleaning is performed by combining mechanical stirring and ultrasonic cleaning, and the cleaning time is 30-60 minutes.

[0008] Furthermore, in the extrusion molding step of the molding process, the extrusion temperature is set to be controlled at 230-260° C. and the extrusion speed is set to be 5-8 m / min.

[0009] Further, the blending temperature is set to 220° C. to 250° C., the screw speed is set to 300-400 rpm, and the blending time is set to 15-25 minutes.

[0010] Beneficial technical effects: 1. Improved optical performance The optical properties of architectural skylights made from waste polycarbonate plastic modified with 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenylsulfone are significantly improved. The functional groups in the compound interact with the polycarbonate plastic, optimizing the molecular arrangement inside the material, so that the light transmittance of the skylight can be increased to more than 90% and the haze is reduced to less than 10%, thereby providing better lighting effects and indoor visual comfort. In practical applications, this means that indoors can get more sufficient and more uniform natural lighting, reducing the use of artificial lighting and reducing energy consumption.

[0011] 2. Enhanced mechanical properties Through the chemical bonding and physical interaction between 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone and waste polycarbonate plastic, the mechanical properties of the material are significantly improved. In the tensile strength test, the average tensile strength of the building skylight board prepared according to the method of the present invention can reach 80-100MPa, which is about 50%-80% higher than the skylight board prepared from traditional unmodified waste polycarbonate plastic; in the impact strength test, the average impact strength can reach 150-200J / m², which is about 80%-120% higher than the skylight board prepared from traditional unmodified waste polycarbonate plastic, so that it can better withstand external impact and loads in the natural environment, and improve the service life and safety of the skylight board.

[0012] 3. Improved processing performance The presence of 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone improves the processing performance of waste polycarbonate plastics. During the melt blending and extrusion molding process, due to the role of functional groups such as ether bonds, the fluidity of the material is enhanced, making it easier to extrude and mold in the extruder, reducing the processing difficulty, improving the product qualification rate, and also reducing the energy consumption in the processing process, thereby reducing the production cost.

[0013] 4. Significant environmental benefits The present invention uses waste polycarbonate plastic as the main raw material, effectively reduces the pollution of waste plastic to the environment, realizes the recycling of resources, meets environmental protection requirements, and has important environmental and social benefits. By recycling waste polycarbonate plastic, not only precious raw materials are saved, but also the burden on landfills and the pressure on the environment are reduced.

[0014] 5. Multifunctional performance integration The skylight board prepared by this method not only has excellent lighting performance, but also has excellent fire resistance, UV resistance and thermal insulation performance. Through the interaction between the modified compound and the polycarbonate plastic and the special treatment during the processing, the fire resistance level of the skylight board reaches B1 or above, which can effectively prevent the spread of fire; the reasonable use of anti-ultraviolet additives and the structural characteristics of the material itself greatly improve its anti-ultraviolet performance and slow down the aging speed of the material; in addition, the special formula and structural design of the material also give it a certain thermal insulation effect, reducing the energy consumption of the building and improving energy utilization efficiency. DETAILED DESCRIPTION

[0015] Example 1 Waste polycarbonate plastic materials are widely collected from various sources that may generate waste polycarbonate plastics, such as electronic and electrical waste dismantling plants, construction waste recycling stations, and plastic product recycling points. For example, in a large-scale collection activity, about 800 kilograms of waste polycarbonate plastics were collected from multiple electronic and electrical waste dismantling plants. These waste plastics mainly came from waste computer monitors, laptop computer shells, TV shells, and some architectural decorative plastic products.

[0016] Cleaning: Use professional detergents and clean water to clean the collected waste polycarbonate plastics several times to remove dirt, oil and other impurities on the surface. The specific operation is to put the waste polycarbonate plastics into a large cleaning tank, add an appropriate amount of detergent water solution, and use a combination of mechanical stirring and ultrasonic cleaning to thoroughly clean them. The cleaning time is about 30-60 minutes to ensure that all surface impurities are removed. Drying: Put the cleaned waste polycarbonate plastics into a drying oven and dry them at a temperature of 60-80℃ for 4-6 hours. The water content of the plastic is controlled below 0.3% to ensure the quality of subsequent processing. Crushing: The dried waste polycarbonate plastics are crushed into small particles by a crusher, and the particle size is controlled between 1-3 mm. Set the crusher speed to 1000-1500 rpm and the crushing time to 20-30 minutes to obtain small particles of uniform particle size, which is convenient for subsequent mixing with modified compounds.

[0017] Synthetic modified compounds, a new modified organic compound named 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone is synthesized through a specific chemical reaction, which is used to modify waste polycarbonate plastics to meet the performance requirements of building skylights. Synthesis principle: 4,4'-dihydroxydiphenyl sulfone and 3-chloro-1-propanol are used as raw materials and reacted under alkaline conditions. Specifically, under the action of sodium hydroxide as a catalyst, the hydroxyl group in 4,4'-dihydroxydiphenyl sulfone and the chlorine atom in 3-chloro-1-propanol undergo a substitution reaction, accompanied by a series of reactions such as intermolecular condensation, and finally 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone is generated. .

[0018] Compound structure and functional group characteristics: The molecular formula of the final product compound is C21H20O5S, which contains multiple benzene ring structures, with functional groups such as hydroxyl (-OH) and ether bond (-O-) connected to the benzene ring. The benzene ring structure gives the material good rigidity and heat resistance, allowing it to maintain good shape and performance stability in the use environment of building skylights; hydroxyl can enhance the binding force with polycarbonate plastic, interact with the functional groups in polycarbonate plastic through hydrogen bonds and other effects, and can participate in subsequent possible cross-linking reactions, which helps to improve the mechanical strength and overall stability of the material; ether bonds increase the flexibility and water resistance of the material, allowing the skylight to have better adaptability under different environmental conditions and not easily damaged by factors such as water erosion.

[0019] Specific synthesis steps: In a three-necked flask with a stirrer, a thermometer and a reflux condenser, add 400 grams of 4,4'-dihydroxydiphenyl sulfone and 300 grams of 3-chloro-1-propanol, and then slowly add 200 grams of sodium hydroxide as a catalyst. The reaction system is placed in an oil bath, the reaction temperature is controlled at 80-100°C, the stirring speed is set to 400-600 rpm, and the reaction time is about 5-7 hours. After the reaction is completed, a series of post-treatment steps are performed, including neutralization with a dilute hydrochloric acid solution, washing to remove excess alkali, and then drying with anhydrous sodium sulfate. Finally, pure 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone is obtained by recrystallization and other methods, and the yield is about 500-600 grams.

[0020] The pretreated waste polycarbonate plastic particles are mixed with the synthesized modified compound at a mass ratio of 1:6 to 1:3. For example, 12 kg of crushed waste polycarbonate plastic particles and 2-4 kg of modified compound are put into a high-speed mixer, and the stirring speed is set to 900-1200 rpm for 25-35 minutes to ensure that the modified compound is evenly distributed in the waste polycarbonate plastic particles to prepare for subsequent melt blending.

[0021] The mixed materials are placed in a twin-screw extruder for melt blending, with the temperature set at 220°C to 250°C, the screw speed at 300-400 rpm, and the blending time at 15-25 minutes. Under the action of the twin-screw extruder, the modified compound is fully mixed with the waste polycarbonate plastic to form a uniform composite material. The components interact through physical and chemical bonding, significantly improving the comprehensive performance of the material.

[0022] Extrusion molding: The melt-blended composite material is extruded through an extruder into the plate shape required for the building skylight. According to actual needs, the extruder's die size and extrusion speed and other parameters are adjusted to obtain a skylight prototype of suitable thickness and size. For example, the extrusion temperature is set at 230-260℃, the extrusion speed is 5-8 meters / minute, and the extrusion thickness can be adjusted between 2-10 mm according to the specific design requirements of the building skylight.

[0023] Cooling and shaping: The extruded skylight board prototype is cooled and shaped in a cooling device. The cooling time is set to 15-30 minutes, and the water temperature is controlled at 20-30°C. The skylight board is slowly cooled and shaped to obtain the final building skylight board product.

[0024] Example 2

[0025] Waste polycarbonate plastic collection: About 800 kg of waste polycarbonate plastic was collected from multiple electronic and electrical waste dismantling plants. These waste plastics mainly come from waste computer monitors, laptop shells, TV shells, and some architectural decorative plastic products. The collection process requires careful sorting to separate waste polycarbonate plastic from other waste to ensure the purity of the collected plastic.

[0026] Pretreatment cleaning: Put the waste polycarbonate plastic into a large cleaning tank, add an appropriate amount of detergent water solution, and use a combination of mechanical stirring and ultrasonic cleaning to thoroughly clean it. The cleaning time is about 30-60 minutes to ensure that all surface dirt, oil and other impurities are removed. Drying: Put the cleaned waste polycarbonate plastic into a drying oven and dry it at a temperature of 60-80°C for 4-6 hours. The water content of the plastic is controlled below 0.3% to ensure the quality of subsequent processing. Crushing: The dried waste polycarbonate plastic is crushed into small particles by a crusher, and the particle size is controlled between 1-3 mm. Set the crusher speed to 1000-1500 rpm and the crushing time to 20-30 minutes to obtain small particles of uniform particle size for subsequent mixing with modified compounds.

[0027] The specific synthesis steps of the modified compound are as follows: 400 grams of 4,4'-dihydroxydiphenyl sulfone and 300 grams of 3-chloro-1-propanol are added to a three-necked flask with an agitator, a thermometer and a reflux condenser, and then 200 grams of sodium hydroxide is slowly added as a catalyst. The reaction system is placed in an oil bath, the reaction temperature is controlled at 80-100°C, the stirring speed is set to 400-600 rpm, and the reaction time is about 5-7 hours. After the reaction is completed, a series of post-treatment steps are performed, including neutralization with a dilute hydrochloric acid solution, washing to remove excess alkali, and then drying with anhydrous sodium sulfate. Finally, pure 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone is obtained by recrystallization and the like, with a yield of about 500-600 grams.

[0028] Take 12 kg of crushed waste polycarbonate plastic particles and put them into a high-speed mixer with 2-4 kg of the modified compound. Set the stirring speed to 900-1200 rpm and the stirring time to 25-35 minutes to ensure that the modified compound is evenly distributed in the waste polycarbonate plastic particles.

[0029] The mixed materials are placed in a twin-screw extruder for melt blending, with the temperature set at 220°C to 250°C, the screw speed at 300-400 rpm, and the blending time at 15-25 minutes. Under the action of the twin-screw extruder, the modified compound is fully mixed with the waste polycarbonate plastic to form a uniform composite material. The components interact through physical and chemical bonding, significantly improving the comprehensive performance of the material.

[0030] Extrusion molding: The melt-blended composite material is extruded into the required board shape of the building skylight through an extruder. According to actual needs, the extruder's die size and extrusion speed and other parameters are adjusted to obtain a skylight prototype of suitable thickness and size. For example, the extrusion temperature is set at 230-260℃, the extrusion speed is 5-8 meters / minute, and the extrusion thickness can be adjusted between 2-10 mm according to the specific design requirements of the building skylight.

[0031] Cooling and shaping: The extruded skylight board prototype is cooled and shaped in a cooling device. The cooling time is set to 15-30 minutes, and the water temperature is controlled at 20-30°C. The skylight board is slowly cooled and shaped to obtain the final building skylight board product.

[0032] Example 3

[0033] Optical performance comparison test Experimental setup: Prepare traditional building skylights (using new polycarbonate plastic that has not been treated by the improved method of the present invention), materials using only waste polycarbonate plastic that has not been treated with 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone, and building skylights prepared according to the method of the present invention, and prepare 5 parallel samples for each sample to ensure the accuracy of the data.

[0034] Test items and results: Light transmittance test: The light transmittance test was conducted using a light transmittance tester in accordance with relevant standards. The results showed that the average light transmittance of traditional building skylights was about 80%, and the average light transmittance of materials treated with only waste polycarbonate plastics without adding 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone was about 70%, while the average light transmittance of the building skylights prepared according to the method of the present invention could reach more than 90%, which was about 12.5% ​​higher than that of traditional building skylights, and about 28.5% higher than that of waste polycarbonate plastics without adding 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone.

[0035] Haze test: The haze test was performed using a haze meter. The average haze value of traditional building skylights is about 15%, and the average haze value of discarded polycarbonate plastics without adding 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone is about 20%. The average haze value of the building skylights prepared by the present invention is less than 10%, which is about 33.3% lower than that of traditional building skylights, and about 50% lower than that of discarded polycarbonate plastics without adding 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone.

[0036] Example 4 Collection of waste polycarbonate plastics: About 900 kg of waste polycarbonate plastics were collected from various waste plastic recycling stations, electronic equipment dismantling plants, and building demolition sites. These waste plastics mainly come from waste computer accessories, plastic pipes, plastic products for building decoration (such as plastic wall panels, ceiling decorative panels, etc.), and some industrial equipment shells. During the collection process, the staff used professional sorting equipment and combined manual screening to carefully separate the waste polycarbonate plastics from other mixed wastes to ensure that the collected waste polycarbonate plastics were of high purity and met the requirements of subsequent processing.

[0037] Cleaning: Put the collected waste polycarbonate plastics into a large cleaning tank, add an appropriate amount of specially developed high-efficiency environmentally friendly detergent and water. Use mechanical stirring and ultrasonic cleaning to perform deep cleaning. The mechanical stirring speed is set to 250-350 revolutions per minute, and the ultrasonic cleaning frequency is set to 1000-1500 Hz. The cleaning time is about 35-65 minutes, so as to ensure that the dirt, oil, dust and other impurities on the surface of the waste polycarbonate plastics can be completely removed.

[0038] Drying: After cleaning, the waste polycarbonate plastic is transferred to a water-covered area and dried at a temperature range of 62-82℃ for 4.5-6.5 hours. The moisture content of the plastic is accurately controlled below 0.28%, laying a good foundation for subsequent crushing and other processing procedures and ensuring processing quality.

[0039] Crushing: The dried waste polycarbonate plastic is sent to the crusher for crushing, and the particle size of the crushed waste polycarbonate plastic particles is controlled between 0.9 and 2.2 mm. By setting the crusher speed to 1100-1400 rpm and the crushing time to 22-32 minutes, small particles with relatively uniform particle size are obtained, which is convenient for subsequent full mixing with modified compounds and unreported organic compounds.

[0040] Modified compound synthesis steps: The compound named 2-(hydroxymethyl)-5-methyl-1,3-oxazole (hereinafter referred to as compound F) is synthesized. Its design principle is based on the multi-faceted consideration of improving the comprehensive performance of building skylight panels. It aims to optimize the optical, mechanical and weather resistance properties of skylight panels through its unique molecular structure and functional group characteristics, synergistic effects with waste polycarbonate plastics and modified compounds. The synthesis operation is carried out in a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a gas flow controller. First, 200 grams of 1,3-oxazole, 150 grams of formaldehyde and 120 grams of sodium hydroxide are added to the four-necked flask as basic raw materials and catalysts. Then, ethylene oxide gas is slowly introduced through the gas flow controller, and the gas introduction rate is controlled to be 8-12 ml per minute. At the same time, the reaction system is placed in an oil bath pot, the reaction temperature is set at 85-105°C, and the stirring speed is maintained at 450-650 rpm. The reaction lasts for 5-7 hours, during which the reaction progress is closely monitored and various parameters are adjusted in a timely manner according to the reaction conditions. After the reaction is completed, a series of meticulous post-treatment steps are performed, including neutralization with dilute hydrochloric acid solution to remove excess alkali, multiple water washings to clean impurities, drying with anhydrous magnesium sulfate, and finally vacuum distillation to obtain pure compound F, with a yield of about 280-380 grams.

[0041] The molecular structure of compound F has been carefully designed to introduce a variety of functional groups to achieve effective synergy with waste polycarbonate plastics and other additives. It contains structural units such as oxazole ring, hydroxymethyl and methyl. It is expected that the comprehensive performance of the light-transmitting board will be improved through the interaction between these structural units and the components in the system. Oxazole ring structure: This ring structure has a certain rigidity and chemical stability. After forming a composite material, it can enhance the overall structural strength of the material, help maintain the shape stability of the light-transmitting board under different environmental conditions, and prevent deformation or damage caused by external forces, temperature changes and other factors. At the same time, in the process of interacting with other components, the oxazole ring can form specific chemical bonds or physical adsorption with certain functional groups in the molecular chain of waste polycarbonate plastics and modified compounds, further improving the cohesion of the material, thereby improving the mechanical properties of the light-transmitting board. Hydroxylmethyl (-CH2OH) group: The hydroxymethyl group has a strong polarity and can combine with functional groups such as carbonyl in waste polycarbonate plastics through hydrogen bonding. This hydrogen bonding effect not only enhances the compatibility between compound F and waste polycarbonate plastic, allowing compound F to be more evenly distributed throughout the system, but also adjusts the microstructure of the material to make the material denser, thereby improving the refraction and reflection properties of the skylight to light and optimizing its optical properties. In addition, hydroxymethyl groups may also participate in some subsequent chemical reactions, such as forming a cross-linked structure with other additives, further enhancing the stability of the material. Methyl (-CH3) group: The presence of methyl groups increases the stability of compound F molecules, making it less prone to chemical changes such as decomposition during processing and during the use of skylights. At the same time, methyl groups can adjust the solubility of compound F, allowing it to be better dispersed in the system when mixed with other ingredients, which is conducive to forming a uniform composite material, thereby improving the overall performance of the skylight.

[0042] Mixing modification: Take 15 kg of crushed waste polycarbonate plastic particles, first put them into a high-speed mixer with 3-5 kg ​​of modified compounds, set the stirring speed to 1000-1300 rpm, and stir for 30-40 minutes to make the modified compounds evenly distributed in the waste polycarbonate plastic particles. Then add 2-3 kg of the above-synthesized unreported organic compound compound F, and continue stirring at the same stirring speed for 20-30 minutes to ensure that compound F can also be evenly dispersed in the mixture, so as to fully prepare for the subsequent melt blending.

[0043] Melt blending: The mixed materials are placed in a twin-screw extruder for melt blending, the temperature is set to 230°C to 260°C, the screw speed is 350-450 rpm, and the blending time is 20-30 minutes. Under the action of the twin-screw extruder, the modified compound, the unreported organic compound and the waste polycarbonate plastic are fully mixed to form a uniform composite material. The components interact through physical and chemical bonding, which significantly improves the comprehensive performance of the material.

[0044] Extrusion molding: The melt-blended composite material is extruded into the plate shape required for the building skylight through an extruder. The die size and extrusion speed of the extruder can be flexibly adjusted according to actual needs. For example, the extrusion temperature can be set at 240-270℃, the extrusion speed can be set at 6-9 m / min, and the extrusion thickness can be adjusted between 3-12 mm according to the design requirements of the specific building skylight, so as to obtain a skylight prototype of suitable thickness and size.

[0045] Cooling and shaping: The extruded skylight board prototype is cooled and shaped in a cooling device. The cooling time is set to 20 - 35 minutes, and the water temperature is controlled at 22 - 32°C. The skylight board is slowly cooled and shaped to obtain the final building skylight board product.

[0046] Waste polycarbonate plastics were collected and pretreated according to the method in the embodiment to synthesize modified compounds and unreported organic compounds. Traditional new polycarbonate plastics and conventional additives for polycarbonate plastic modification (polycarbonate resin additives) were prepared as prior art materials for comparative tests. Experimental grouping: Experimental group: According to the method of Example 4, waste polycarbonate plastics, modified compounds and unreported organic compounds were used to prepare building skylights. Control group 1: New polycarbonate plastics were used, and no modified compounds and unreported organic compounds were added. Building skylights were prepared according to conventional extrusion molding processes. Control group 2: Waste polycarbonate plastics were used, and only conventional additives for polycarbonate plastic modification (polycarbonate resin additives) were added. Building skylights were prepared according to conventional extrusion molding processes. The three samples were tested for light transmittance using a transmittance tester in accordance with relevant standards. Five test points were selected at different locations for each sample, and the average value was taken as the light transmittance result of the sample. The three samples were tested for haze using a haze meter. Five test points were also selected at different locations for each sample, and the average value was taken as the haze result of the sample. The tensile strength, flexural strength and impact strength tests were carried out on the three samples in accordance with the corresponding national standards. Five specimens were tested for each sample and the average value was taken as the final result.

[0047] Test results: The average light transmittance of the building skylight panels prepared in the test group can reach more than 92%, which is about 15% higher than the traditional building skylight panels in the control group 1 (the average light transmittance is about 80%), and about 27.7% higher than the control group 2 which only uses waste polycarbonate plastics with conventional additives (the average light transmittance is about 72%). The average haze of the building skylight panels prepared in the test group is less than 8%, which is about 46.7% lower than the traditional building skylight panels in the control group 1 (the average haze is about 15%), and about 63.6% lower than the waste polycarbonate plastics without adding unreported organic compounds in the control group 2 (the average haze is about 22%). The average tensile strength of the test group reached more than 75MPa, the average tensile strength of the control group 1 was about 60MPa, and the average tensile strength of the control group 2 was about 50MPa. The test group increased by more than 25% compared with the control group 1, and increased by more than 50% compared with the control group 2. The average bending strength of the test group reached more than 120MPa, the average bending strength of the control group 1 was about 95MPa, and the average bending strength of the control group 2 was about 80MPa. The test group increased by about 26.3% compared with the control group 1, and increased by about 50% compared with the control group 2. The average impact strength of the test group reached more than 100kJ / m², the average impact strength of the control group 1 was about 75kJ / m², and the average impact strength of the control group 2 was about 60kJ / m². The test group increased by about 33.3% compared with the control group 1, and increased by about 66.7% compared with the control group 2.

[0048] Through comparative experiments with the prior art, it can be seen that the method of preparing building skylight panels using waste polycarbonate plastics, modified compounds and unreported organic compounds has a significant synergistic effect in terms of light transmittance, haze and mechanical properties, can effectively improve the comprehensive performance of building skylight panels, and has good application prospects and economic benefits.

Claims

1. A method for preparing a building lighting panel using waste polycarbonate plastic, characterized in that: The following steps are involved: (1) Collection of waste polycarbonate plastics; (2) Washing the collected waste polycarbonate plastics, placing the washed waste polycarbonate plastics in a drying oven, and drying them at a temperature of 60-80°C for 4-6 hours to control the water content of the plastics to be below 0.3%; crushing the dried waste polycarbonate plastics into small particles by a crusher, with the particle size controlled between 1-3 mm; (3) Synthesis of modified organic compounds: 4,4'-dihydroxydiphenyl sulfone and 3-chloro-1-propanol are used as raw materials and reacted under alkaline conditions with sodium hydroxide as a catalyst to synthesize a modified organic compound named 3-(4-hydroxyphenoxy)-1-propoxy-4-phenoxyphenyl sulfone; the synthesis comprises the following specific steps: 400 g of 4,4'-dihydroxydiphenyl sulfone and 300 g of 3-chloro-1-propanol are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and then 200 g of sodium hydroxide is slowly added as a catalyst, the reaction system is placed in an oil bath, the reaction temperature is controlled at 80-100°C, the stirring speed is set to 400-600 rpm, the reaction time is 5-7 hours, after the reaction is completed, the mixture is neutralized and washed with a dilute hydrochloric acid solution to remove excess alkali, and then dried with anhydrous sodium sulfate, and finally the modified organic compound is obtained in pure form by recrystallization or the like; (4) Mixing modification: mixing the pretreated waste polycarbonate plastic particles with the synthesized modified organic compound in a mass ratio of 1:6 to 1:3; (5) Melt blending: The mixed materials are placed in a twin-screw extruder for melt blending; (6) Extruding the melt-blended composite material into the required plate shape of the building skylight through an extruder, and adjusting the die size and extrusion speed parameters of the extruder so that the extrusion thickness can be adjusted between 2 and 10 mm according to the design requirements of the specific building skylight; cooling and shaping the skylight prototype after extrusion in a cooling device to obtain the final building skylight product.

2. The method according to claim 1, characterized in that By setting the stirring speed to 900-1200 rpm and the stirring time to 25-35 minutes, it is ensured that the modified organic compound is evenly distributed in the waste polycarbonate plastic particles.

3. The method according to claim 1, characterized in that In the cleaning step of the pretreatment, cleaning is performed by combining mechanical stirring and ultrasonic cleaning, and the cleaning time is 30-60 minutes.

4. The method according to claim 1, characterized in that: In the extrusion molding step of the molding process, the extrusion temperature is set to be controlled at 230-260° C. and the extrusion speed is set to be 5-8 m / min.

5. The method according to claim 1, characterized in that The blending temperature was set at 220°C to 250°C, the screw speed was set at 300-400 rpm, and the blending time was set at 15-25 minutes.